Mathematical modeling, design, and predictive control of a boost converter - Soares, Alexandre Filgueira (2024)
Boost converters are widely used to raise the output voltage to a level higher than the input voltage of various systems. These converters are commonly used in batteries for electric automobiles, regenerative braking of DC motors, quadrirotors, solar chargers, power audio amplifiers and many other devices. To do this, this device stores energy in the magnetic field of an inductor and then transfers this energy to a capacitor in such a way that the voltage of the capacitor can increase beyond the voltage of the source that supplied energy to the inductor. However, to obtain a desired voltage at the output, it is essential to use a reliable controller to regulate this system. This article presents mathematical modeling, sizing design according to established specifications and predictive control of a boost converter. The control strategy used to regulate the voltage of this converter is a deadbeat controller, which has a simple structure, but provides fast response to the closed-loop system. The numerical simulation results demonstrate the superiority of the predictive controller over a proportional-integral-derivative controller.